Exceptional electrocatalytic oxygen evolution via tunable charge transfer interactions in La0.5Sr1.5Ni1−x Fe x O4±δ Ruddlesden-Popper oxides - Robin P. Forslund (Nature Portfolio, 2018)
Water electrolysis provides a potential means to large-scale renewable fuel generation, although sluggish oxygen evolution kinetics challenges progress. Here, authors report on Ruddlesden–Popper oxides as active oxygen evolution electrocatalysts that provide impetus for overcoming kinetic barriers.